An Overview of Small Farm Direct Marketing - Mickie E. Swisher; James Sterns (EDIS, 2003)
Direct marketing refers to selling that is based on a personal, one-to-one relationship that ties farmers and consumers together. Many times this relationship is face-to-face, like at farmers' markets. Other times, the consumer and farmer may not actually meet, for example, Internet sales. This document is FCS 7211, one of a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: June 2003.